Book(s) Review: The Medical Library Association Guide to Data Management for Librarians and Data Management: A Practical Guide for Librarians - T. Scott Plutchak (Journal of eScience Librarianship, 2017)
Book reviews of: The Medical Library Association Guide to Data Management for Librarians, edited by Lisa Federer, Rowman & Littlefield, Copyright 2016 by Medical Library Association ISBN 978-1-4422-6428-1; and, Data Management: A Practical Guide for Librarians, by Margaret E. Henderson, Rowman & Littlefield Publishers, 2017 ISBN 978-1-4422-6439-7.